Role of Follicle-Stimulating Hormone in Spermatogenesis - Oduwole, Olayiwola O.; Peltoketo, Hellevi; Huhtaniemi, Ilpo T. (Frontiers in Endocrinology, 2018)
Spermatogenesis is a concerted sequence of events leading to the formation of mature spermatozoa. This process involves differential gene-expression and cell-cell interplay that is regulated by key endocrine stimuli, follicle-stimulating hormone (FSH) and luteinizing hormone (LH). FSH affects independently and in concert with LH-stimulated testosterone, the proliferation, maturation and structure of the supporting Sertoli cells as well as metabolism and transport of regulatory signals and nutrients to the developing germ cells. Rodents are able to complete spermatogenesis without FSH stimulus, but its deficiency significantly decreases sperm quantity. Men carrying loss-of-function mutation in the gene encoding the ligand or its receptor, FSHB or FSHR respectively, present with azoospermia and mildly suppressed spermatogenesis. Recently, the importance of high intratesticular testosterone concentration has been questioned and it has been established that spermatogenesis can be completed with minor amount of the hormone, though at the expense of sperm quantity. Furthermore, we have recently demonstrated that very robust constitutive FSHR action can rescue spermatogenesis and fertility in mice even when testosterone stimulus is completely blocked. The clinical relevance of these findings is evidence for a new strategy of high-dose FSH in treatment of spermatogenic failure.